The Role of Work Discipline and Communication on Non-Civil Servant Performance: A Case Study of Tanah Bumbu Regency - Jakiroh Jakiroh; Sutrisno Sutrisno; Melania Melania; Rudy Hartanto; Sriyunia Anizar (Faculty Of Islamic Economics and Business, 2025)
Purpose: This study aims to analyze the effect of work discipline and communication on the performance of non-civil servant employees (non-ASN) at the Human Resources Development and Personnel Agency (BKPSDM) of Tanah Bumbu Regency.Methodology: The research adopts a quantitative approach using a survey method. A total of 32 non-ASN employees participated as respondents, selected using a census sampling technique. Data were collected through a validated and reliable questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), including path analysis and bootstrapping to test the significance of the relationships among variables.Research Findings: The results reveal that communication has a positive and significant effect on employee performance, with a path coefficient of 1.155, T-statistic 6.946 (> 1.96), and p-value 0.000 (< 0.05). Conversely, work discipline also has a significant yet negative effect on employee performance, with a path coefficient of –0.433, T-statistic 2.173 (> 1.96), and p-value 0.015 (< 0.05). Simultaneously, communication emerges as the dominant factor in enhancing employee performance, whereas rigid disciplinary practices tend to have an adverse relationship with performance.Contribution: This study contributes empirical evidence by simultaneously examining the effects of communication and work discipline on the performance of non-ASN employees in the local government sector, an area that has received limited scholarly attention. The findings provide novel insights that overly formalistic and punitive disciplinary practices may reduce performance, suggesting that public organizations should adopt more constructive and humanistic disciplinary approaches supported by effective communication to improve employee outcomes. Tujuan Penelitian: Penelitian ini bertujuan untuk mengetahui pengaruh disiplin kerja dan komunikasi terhadap kinerja pegawai non Aparatur Sipil Negara (ASN) di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Tanah Bumbu.Metodologi: Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Sebanyak 32 pegawai non ASN menjadi responden penelitian, yang dipilih secara sensus. Data dikumpulkan melalui kuesioner yang telah diuji validitas dan reliabilitasnya, kemudian dianalisis menggunakan pendekatan Structural Equation Modeling (SEM) berbasis Partial Least Squares (PLS) dengan pengujian jalur (path analysis) dan bootstrapping untuk menguji signifikansi pengaruh antarvariabel.Temuan Penelitian: Hasil penelitian menunjukkan bahwa komunikasi berpengaruh positif dan signifikan terhadap kinerja pegawai dengan koefisien jalur 1,155, T-statistic 6,946 (> 1,96), dan p-value 0,000 (< 0,05). Sebaliknya, disiplin kerja juga berpengaruh signifikan namun dengan arah negatif terhadap kinerja pegawai, dengan koefisien jalur –0,433, T-statistic 2,173 (> 1,96), dan p-value 0,015 (< 0,05). Secara simultan, komunikasi menjadi faktor dominan dalam peningkatan kinerja pegawai, sedangkan disiplin kerja yang kaku justru menunjukkan hubungan berlawanan dengan kinerja.Kontribusi: Penelitian ini memberikan kontribusi empiris dengan menguji secara simultan pengaruh komunikasi dan disiplin kerja pada kinerja pegawai non ASN di sektor pemerintahan daerah, yang masih jarang dilakukan pada penelitian sebelumnya. Temuan ini juga memberikan wawasan baru bahwa penerapan disiplin yang terlalu formalistik dapat berdampak negatif, sehingga organisasi publik perlu merancang strategi disiplin yang lebih konstruktif dan humanis disertai komunikasi efektif untuk meningkatkan kinerja pegawai.